International emissions trading with endogenous taxes - Odd Godal; Bjart Holtsmark (Statistics Norway, Research Department, 2010)
Abstract: Motivated by the climate problem, this paper examines some effects of international cap & trade when national quotas result from strategic choice. In contrast to the fairly optimistic tone of closely related literature, the tenor of our results is pessimistic. We find that though an international permit market may flourish, it will mainly redistribute income. As far as emissions reductions are concerned, the classical, rather inefficient, noncooperative outcome will prevail, regardless of the presence of cap & trade.
Keywords: C72; D62; Q54; 330; International emissions trading; global externality; endogenous endowments; emissions taxes.